Ownership structure, corporate governance and earnings management in China / Li Honglin - Li , Honglin (2021)
To address the inherent inefficiencies of state-owned enterprises (SOEs), China has adopted partial and gradual privatization reforms and a series of corporate governance reforms, such as introducing independent directors and audit committees, and reestablishing audit firms. These reforms have resulted in the emergence and rise of private-owned enterprises (POEs) and improved the management efficiency of SOEs in China. Driven by the stronger earnings management motivations of POEs and the potentially greater effect of corporate governance in POEs, this study is conducted to examine whether Chinese SOEs perform a lower level of earnings management than Chinese POEs and whether corporate governance mechanisms (i.e. board independence, audit committee independence and external auditor) can moderate the difference in earnings management between them. This study selects 582 A-share companies from the Shanghai Stock Exchange (SHSE) and Shenzhen Stock Exchange (SZSE) from 2015 to 2018. The conceptual framework of the study is deduced based on agency theory and the non-profit goals of SOEs. The results show that SOEs perform a lower level of earnings management than POEs in China. The explanation for this phenomenon is that the non-profit goals of SOEs and the Chinese government long-term protection have relatively alleviated the principal-agent conflicts within SOEs, thereby reducing their motivations to manipulate earnings. Results also show that Big 4 firms can effectively reduce the difference in earnings management between Chinese SOEs and POEs. It is attributed to the more severe principal-agent conflicts within POEs and their stronger motivations to manage earnings. Hence, Big 4 firms are faced with higher constraining effects on the earnings management of POEs.